Bivalirudin use in patients undergoing percutaneous coronary intervention for acute myocardial infarction. Insights from the prospective, multi-centre EUROVISION registry. (December 2014) - Limbruno, U.; Picchi, A.; Galli, S.; Huber, K.; Lipiecki, J.; Bernstein, D.; Deliargyris, E.; Anthopoulos, P.; Nienaber, C.; Hamon, M.
Abstract Background: The effectiveness of bivalirudin in patients undergoing percutaneous coronary intervention for acute myocardial infarction has been tested in clinical trials, but its use in a real-world scenario has never been reported. Methods: From the total number of patients enrolled in the EUROVISION registry, 678 subjects affected by ST-elevation myocardial infarction were selected and included in the analysis. Posology and usage patterns of bivalirudin, as evaluated by dose and time of drug bolus and infusion administered, were evaluated. The 30-day outcome has been assessed by efficacy and safety endpoints. Results: All patients received an initial intravenous bolus of bivalirudin (0.70 ± 0.25 mg/kg) followed by an infusion (1.58 ± 0.47 mg/kg/h; duration: 60 [30, 107] min) in 99.3% of cases. An additional bolus (0.49 ± 0.06 mg/kg) was administered in 9.3% of patients. Bivalirudin infusion was prolonged after procedure in 62.2%. Death occurred in 2.1% of patients, non-fatal myocardial reinfarction in 0.3%, unplanned revascularization in 0.6% and non-fatal stroke in 0.4%. Acute stent thrombosis was not observed. Major bleeding occurred in 1.5% of patients. Conclusions: Bivalirudin usage in the setting of primary PCI provided excellent results in terms of 30-day outcome even in a real-world population.